Atoning Past Indulgences: Oral Consumption and Moral Compensation - Schei, Thea S.; Sheikh, Sana; Schnall, Simone (Frontiers in Psychology, 2019)
Previous research has shown that moral failures increase compensatory behaviors, such as prosociality and even self-punishment, because they are strategies to re-establish one’s positive moral self-image. Do similar compensatory behaviors result from violations in normative eating practices? Three experiments explored the moral consequences of recalling instances of perceived excessive food consumption. In Experiment 1 we showed that women recalling an overeating (vs. neutral) experience reported more guilt and a desire to engage in prosocial behavior in the form of so-called self-sacrificing. In Experimental 2 this logic was applied to actual spontaneous helping behaviors toward an experimenter, with participants who recalled an overeating (vs. neutral) experience exhibiting more such helping in the laboratory. Experimental 3 expanded the investigation to self-inflicted pain: overeating (vs. neutral) recall led to higher levels of self-punishment as indicted by longer time periods spent engaging in the cold pressor task. In sum, failures in normative food consumption can be viewed as moral transgressions that elicits both interpersonal and intrapersonal compensatory behaviors aimed at restoring a positive moral self-image.